PUMP DESIGN AND COMPUTATIONAL FLUID DYNAMIC ANALYSIS FOR HIGH TEMPERATURE SULFURIC ACID TRANSFER SYSTEM - JUNG-SIK CHOI; YOUNG-JOON SHIN; KI-YOUNG LEE; YONG-SUP YUN; JAE-HYUK CHOI (Nuclear Engineering and Technology, 2014)
In this study, we proposed a newly designed sulfuric acid transfer system for the sulfur-iodine (SI) thermochemical cycle. The proposed sulfuric acid transfer system was evaluated using a computational fluid dynamics (CFD) analysis for investigating thermodynamic/hydrodynamic characteristics and material properties. This analysis was conducted to obtain reliable continuous operation parameters; in particular, a thermal analysis was performed on the bellows box and bellows at amplitudes and various frequencies (0.1, 0.5, and 1.0 Hz). However, the high temperatures and strongly corrosive operating conditions of the current sulfuric acid system present challenges with respect to the structural materials of the transfer system. To resolve this issue, we designed a novel transfer system using polytetrafluoroethylene (PTFE, Teflon®) as a bellows material for the transfer of sulfuric acid. We also carried out a CFD analysis of the design. The CFD results indicated that the maximum applicable temperature of PTFE is about 533 K (260 °C), even though its melting point is around 600 K. This result implies that the PTFE is a potential material for the sulfuric acid transfer system. The CFD simulations also confirmed that the sulfuric acid transfer system was designed properly for this particular investigation.